Remaking the comedia : Spanish classical theater in adaptation - Erdman, Harley, 1962-; De García, Susan Paun (Colección Támesis. Monografías, 2015)
Leading Golden Age theatre experts examine the ways that comedias have been adapted and reinvented, offering a broad performance history of the genre for scholars and practicioners alike.